Association between Thyroid Status and Glucose Intolerance inHyperthyroid Patients - Wisnu, Wismandari; Soewondo, Pradana; Subekti, Imam (UI Scholars Hub, 2018)
Introduction. The most common endocrinopathy in adults are diabetes mellitus (DM) and thyroid disease. Hyperthyroidism decreases blood glucose control and increased the need of insulin. However, the mechanism of abnormal glucose metabolism in hyperthyroidism is not fully understood. This study aims to determine the relationship of thyroid status with incidence of glucose intolerance in hyperthyroid patients compared to hyperthyroid patients who have achieved clinical status of eutyroid and normal population. Methods. This study was cross sectional design in outpatients with hyperthyroidism in hyperthyroid and euthyroid/subclinical hyperthyroid status, and healthy volunteers who had matching age and sex. An oral glucose test and Homeostatic Model Assesment Insulin Resistance was performed after the diagnosis of hyperthyroidism by FT4 and TSH measurement. Data analysis was performed using SPSS for Windows version 20.0. Results. There were 114 eligible patients (40 case hyperthyroid, 40 case euthyroidism/subclinical hyperthyroidism and 34 healthy subjects). Proportion of glucose intolerance in hyperthyroidism is 52,5% (10% DM, 32,5% impaired glucose tolerance (IGT), and 10% impaired fasting glucose (IFG)), in euthyroidism/subclinical hyperthyroidism was 20% (5% DM, 15% IGT, and 0% IFG), and in healthy subjects was 11,8% (0% DM, 8,8% IGT, and 2,9% IFG). Glucose intolerance in hyperthyroidism was significantly different than euthyroidism/subclinical hyperthyroidism (p=0.002). We also found that the association between thyroid status and glucose intolerance in the group without insulin resistance was significantly different (p=0.004). Conclusions. Our study conclude that there is association between hyperthyroidism and glucose intolerance. Hyperthyroid patients in euthyroidism/subclinical hyperthyroidism status have the same risk as the healthy subject to became glucose intolerance.